Review of research and innovation on novel fertilizers for crop nutrition - Tai McClellan Maaz; Achim Dobermann; Sarah E. Lyons; Allison M. Thomson (npj Sustainable Agriculture)
Abstract Responsible plant nutrition requires innovation to improve nutrient use efficiency across diverse agricultural systems. This review highlights nanofertilizers, biofertilizers, and next-generation enhanced-efficiency fertilizers, examining nutrient-release mechanisms, yield impacts, environmental outcomes, and commercialization challenges. However, limited field data and standardized testing hinder progress. To advance fertilizer research, investments in shared protocols, global research networks, and pre-competitive studies are essential to close knowledge gaps, ensure food security, and reduce environmental harm.